Editorial Introduction to Issue 44 of CSIMQ: The Societal Dimension of Complex Systems - Le Grand, Bénédicte; Ben Rabah, Nourhène (Complex Systems Informatics and Modeling Quarterly, 2025)
This issue of CSIMQ brings together a selection of five articles, each rigorously evaluated according to the following criteria: usefulness, scientific contribution, practical relevance, clarity, and technical quality. The articles included in this issue share a strong societal orientation, addressing challenges and innovations across diverse domains, such as healthcare, citizen services and protection, knowledge management, and sustainable development.